Hermite spline interpolation on patches for parallelly solving the Vlasov-Poisson equation - Crouseilles, Nicolas; Latu, Guillaume; Sonnendrücker, Eric (Zielona Góra: Uniwersytet Zielonogórski)
This work is devoted to the numerical simulation of the Vlasov equation using a phase space grid. In contrast to Particle-In-Cell (PIC) methods, which are known to be noisy, we propose a semi-Lagrangian-type method to discretize the Vlasov equation in the two-dimensional phase space. As this kind of method requires a huge computational effort, one has to carry out the simulations on parallel machines.
Keywords: Vlasov-Poisson equation; semi-Lagrangian method; parallelism